Individual and Regional Factors that Affect Fertility Rates in Five Provinces of Indonesia - Umi Lutfiah; Besral; Milla Herdayati (Makara Journal of Health Research, 2017)
Background: This research paper aims to investigate the individual and regional factors that affect fertility in Indonesia. Methods: This was a crossectional study that analysed data from the 2002-2003, 2007, and 2012 Indonesian Demographic and Health Surveys and the 2012 National Family Planning Coordinating Board Routine Report regarding contraceptive services. The selection criteria for the sample population were married women considered to be of child bearing age (between 15 and 49 years), who had delivered at least one child. Analysis was completed using multilevel logistic regression. Results: Results show that regional factors that affect fertility are influenced by the contraceptive prevalence ratio. The individual factors that affected fertility were the job status of the participant's husband, the level of education attained, the perceived ideal number of children, intervals between births, and previous experience of child mortality. Conclusions: Both central and local governments of provinces with high fertility rates appear to have a lower socio-economic status and require strategic plans that increase expectant mother's participation in education. It is recommended that the National Family Planning Coordinating Board address high fertility rates in Indonesia by way of education. Women of child bearing age who have a low socio-economic status and education level should be targeted to reduce the perceived ideal number of children to 2 and to achieve longer birth intervals (more than 36 months).